(untitled) (Journal of history-rus, 2024)
The history and importance of the development of the "problem of digitization" and "smart city" are discussed as the subject of the article. In this study, the concept of "smart city" is considered as a general vector of further socio-economic development of cities. To reveal the historical aspect of the topic, historical reviews of the digitalization process of countries such as Singapore, Japan, and the USA are given. At this point, research methods: control and mixed methods are used. Using the methodology of qualitative analysis as a research methodology, the author compares the new digitization methodology, its development, developed in domestic discourse, with world experience. The authors come to the conclusion that the transfer of the state management system to a digital format serves as a means of developing the state’s national interests and raising its image in the international arena. Today, the main task is to create conditions for the development of all types of cities, to ensure the uniformity of the economic and social development of the country’s territories at the expense of increasing their competitiveness. Here, not competition, but competition, interaction and mutual aid relations based on the effective use of limited resources, primarily intellectual resources, play a decisive role. The practical importance of the article is to study the history of the complete digitalization of Kazakhstan and put the data into use. The research article will be useful and relevant for all readers who are studying the history of development of modern Kazakhstan or who are studying the humanitarian field. Key words: History of digitization, Global digitization process, Digitized Kazakhstan, Smart city, Transformation, Innovation.